Characteristics of early‐onset pancreatic cancer and its association with familial pancreatic cancer and hereditary pancreatic cancer syndromes. Issue 3 (27th March 2020) - Eguchi, Hidetoshi; Kobayashi, Shogo; Gotoh, Kunihito; Noda, Takehiro; Doki, Yuichiro
Abstract: The incidence of pancreatic cancer is high among those in their sixties to seventies but low in those in their fifties or younger. Although there is no unified definition regarding the age of early‐onset pancreatic cancer, previously published reports suggest that, compared to later‐onset pancreatic cancer patients, early‐onset pancreatic cancer patients tend to be detected at advanced stages and thus have poor prognoses, but they do not show significantly higher rates of patients with genetic factors. On the other hand, it has been reported that patients with familial pancreatic cancer and hereditary pancreatic cancer syndromes often develop pancreatic cancer at a young age. The broad definition of familial pancreatic cancer is pancreatic cancer in patients who have two or more first‐degree relatives with pancreatic cancer; whereas the narrow definition of familial pancreatic cancer is the broad definition of familial pancreatic cancer, while excluding those with inherited tumor syndromes. Hereditary tumors developing pancreatic cancer include hereditary pancreatitis, hereditary breast and ovarian cancer, Peutz‐Jeghers syndrome, familial atypical multiple mole melanoma syndrome, familial adenomatous polyposis, and hereditary non‐polyposis colorectal cancer, all of which are autosomal dominant hereditary diseases. This study reviews the clinical characteristics of early‐onset pancreatic cancer and its association with familial pancreatic cancer and hereditary pancreatic cancer syndromes. Abstract : The incidence of pancreatic cancer is high among those in their sixties to seventies but low in those in their fifties or younger. This study provides an overview of the clinical characteristics of early‐onset pancreatic cancer and its association with familial pancreatic cancer and hereditary pancreatic cancer syndromes.